History, Political Images and Cultural Encounter: The Dutch in the Indonesian Archipelago - Taufik Abdullah (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1994)
In this article, the author describes how the inhabitants of the archipelago, since the first relationship with the Netherlands at the end of the 16th century AD to the present, developing an overview of the various foreign entrants. Various picture developed among the natives of the strangers of particular interest because it reflects the understanding of their relationship with the Dutch settlers. The picture serves as a means to make other people more intelligible to the stranger. The picture also serves as a tool to make the relationship with the stranger seemed more acceptable. Because knowledge of the indigenous population of the Netherlands is increasing, the nature of their relationship with the Netherlands is changing.DOI: 10.15408/sdi.v1i3.848